2008
DOI: 10.1021/la800091y
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Activity of Nanocrystalline Silver Powders and Particles

Abstract: While the activity of the SMAD powders is lower than that of pure silver nitrate, it has the ability to kill bacteria very effectively and over long periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(109 citation statements)
references
References 17 publications
4
103
0
2
Order By: Relevance
“…It has also been reported that Ag-NPs dissolve and generate silver ions, resulting in disruption of ATP production, DNA replication, and ROS generation under certain cellular condition 19,21) . Surface capping of nanoparticles prevented silver ion release, leading to decreased cytotoxicity for cells and organs 22,23) . Therefore, this modification can enhance stability and improve the biocompatibility of these materials 19) .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Ag-NPs dissolve and generate silver ions, resulting in disruption of ATP production, DNA replication, and ROS generation under certain cellular condition 19,21) . Surface capping of nanoparticles prevented silver ion release, leading to decreased cytotoxicity for cells and organs 22,23) . Therefore, this modification can enhance stability and improve the biocompatibility of these materials 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports stated that, the silver nanoparticles have potential antibacterial property against E. coli, S. aureus, Staphylococcus epidermis, Leuconostoc mesenteroides, Bacillus subtilis, Klebsiella mobilis and K. pneumonia (Benn and Westerhoff 2008;Chen and Chiang 2008;Falletta et al 2008;Hernandez-Sierra et al 2008;Ingle et al 2008;Jung et al 2009;Kim 2007;Kim et al 2007Kim et al , 2009Kvitek et al 2008;Raffi et al 2008;Ruparelia et al 2008;Smetana et al 2008;Sondi and Salopek-Sondi 2004;Vertelov et al 2008;Yang et al 2009;Yoon et al 2008a, b). It has been shown that silver nanoparticles prepared with a variety of synthetic methods have effective antimicrobial activity (Lok et al 2006;Baker et al 2005;Aymonier et al 2002;Melaiye et al 2005;Sondi and Salopek-Sondi 2004;Kim et al 2008;Lee et al 2008;Alt et al 2004).…”
Section: Proteus Morganii Staphylococcus Aureusmentioning
confidence: 99%
“…Among these composites, TiO 2 /Ag composites are more potent antibacterial agents due to the fact that Ag nanoparticles (Ag NPs) deposited in TiO 2 matrix act as a conductor and charge separators for blocking electron-hole recombination, resulting in maximizing the production of ROS [15][16][17] . Furthermore, Ag NPs have been known as effective antimicrobial agents with broad-spectrum antibacterial activity, good durability, heat resistance and stability [18,19] . Recently, TiO 2 /Ag composites with different morphologies were prepared by a range of various methods, including UV-irradiation, [16] solvothermal, [20] sol-gel, [21] and chemical deposition [22] .…”
Section: Introductionmentioning
confidence: 99%